solve equation of erf
I used @ndomes' method of using numeric functions, but I still wind up unable to prove that erf... == erf...
:
sage: var('x sigma mu')
sage: assume(sigma > 0)
sage: eq3 = (-erf((sqrt(2)*mu - sqrt(2)*x)/(2*sigma)) == -erf((sqrt(2)*(mu - x))/(2*sigma)))
sage: show(eq3)
sage: show(bool(eq3))
$\newcommand{\Bold}[1]{\mathbf{#1}}-\text{erf}\left(\frac{\sqrt{2} \mu - \sqrt{2} x}{2 \, \sigma}\right) = -\text{erf}\left(\frac{\sqrt{2} {\left(\mu - x\right)}}{2 \, \sigma}\right)$
$\newcommand{\Bold}[1]{\mathbf{#1}}\mathrm{False}$
This slightly simpler equation works correctly however:
sage: eq4 = (-erf((sqrt(2)*mu - sqrt(2)*x)/(sigma)) == -erf((sqrt(2)*(mu - x))/(sigma)))
sage: show(eq4)
sage: show(bool(eq4))
$-\text{erf}\left(\frac{\sqrt{2} \mu - \sqrt{2} x}{\sigma}\right) = -\text{erf}\left(\frac{\sqrt{2} {\left(\mu - x\right)}}{\sigma}\right)$
$\mathrm{True}$
What's going on here?? Is it related to being unable to reduce inverse_erf(erf())
below?
sage: solve(erf(x) == erf(y), x)[0].simplify_full()
x == inverse_erf(erf(y))